(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
In the article, the article addressed pedagogical mechanisms for the formation and development of teaching culture on the students. Pedagogical and psychological properties of reading culture have been identified; The true nature of readership culture and reading culture is explained; It is illuminated by the tools of it.